Discovering gender and coming out: The gender identity journeys and coming out stories of transgender and gender expansive youth. Issue 3 (1st August 2022) - Saltis, Michelle N.; Critchlow, Claire; Fulling-Smith, Jennifer A.
Abstract: This manuscript is a part of a four-part series that presents findings from the first known Interpretative Phenomenological Analysis study of how nine transgender and/or gender expansive youth, aged 13–17, experienced their genders and additional intersecting identities. This manuscript presents the superordinate theme and various sub-themes around the participants' gender identity journeys and coming out processes, including various contextual factors. This collection of themes provides a nuanced look into the complex lives of transgender and gender expansive youth not before explored within the literature through this methodology.